The Effect of Service Quality and Health Facilities on Patient Service Satisfaction at Trimitra Cibinong Hospital - Gisca Lukita Wardhani; Harries Madiistriyatno; Widya Nengsih (Dinasti Publisher, 2026)
The aim of this research is to describe and analyze the influence of service quality on patient satisfaction, to determine and analyze the influence of service quality on patient satisfaction and To determine and analyze the influence of service quality and health facilities together on patient satisfaction at Trimitra Cibinong Hospital. Service Quality (X1) has a significant influence on Patient Satisfaction (Y). This is proven by the results of the t-test which shows a calculated t value of 4.526, greater than the t-table of 1.992, Health Facilities (X2) have a significant effect on Patient Satisfaction (Y). The results of the t-test show a calculated t value of 5.980, which is greater than the t-table of 1.992, so H0 is rejected and Ha is accepted. The magnitude of the influence of the Quality of Health Services and Facilities on Patient Satisfaction is shown by the Adjusted R Square value of 0.605. This means that 60.5% of patient satisfaction is influenced by the quality of health services and facilities, while 39.5% is influenced by other factors not examined in this study.